Identification and commitment in project teams - Chiocchio, F.; Meyer, John (Oxford University Press, 2015)
Organizations today are increasingly using projects in their daily activities. Projects and project-management principles frame goal attainment in academia and many business sectors, and they even serve as theoretical footing for organizational-change endeavors. However, the ubiquity of project management does not mean that project work, project teams, and the ways organizations use projects are well understood. Moreover, while project-management theory and practice aim at providing structure and control to enable successful project completion, an alarmingly high percentage of projects struggle or fail. As the authors of The Psychology and Management of Project Teams explain, this is in part because projects are still mostly managed as technical systems rather than behavioral systems. Even though project-management researchers have become increasingly interested in factors that may have an impact on project-management effectiveness, their efforts fall short of addressing the'human factor.'And, unfortunately, many project-management scholars are largely unaware of the I/O psychology literature--relying, for example, on outdated models of motivation and team development. On the other side, I/O psychologists who research groups and teams often ignore the contextual influences--such as business sector, project type, placement in the organizational hierarchy, and project phase and maturity--that have a crucial impact on how a project will unfold. In this volume, a cross-disciplinary set of editors will bring together perspectives from leading I/O psychology and project-management scholars. The volume will include comprehensive coverage of team selection, development, learning, motivation, and communication; conflict management and well-being; leadership; diversity; performance from a multi-level perspective; and career development. In the concluding chapter, a research agenda will provide a roadmap for an integrated approach to the study of project teams.